Control of neuronal branching by the death receptor CD95 (Fas/Apo-1) - Zuliani, Cecilia; Kleber, Susanne; Kenzelmann, Marc; Kuner, Rohini; Gröne, Hermann-Josef; Herr, Ingrid; Krammer, Peter H.; Martín-Villalba, Ana (Cell death and differentiation, 2006)
The CD95 (Apo-1/Fas)/CD95 ligand (CD95L) system is best characterized as a trigger of apoptosis. Nevertheless, despite broad expression of CD95L and CD95 in the developing brain, absence of functional CD95 (lpr mice) or CD95L (gld mice) does not alter neuronal numbers. Here, we report that in embryonic hippocampal and cortical neurons in vivo and in vitro CD95L does not induce apoptosis. Triggering of CD95 in cultured immature neurons substantially increases neurite branches by promoting their formation. The branching increase occurs in a caspase-independent and death domain-dependent manner and is paralleled by an increase in the nonphosphorylated form of Tau. Most importantly, lpr and gld mutants exhibit a reduced number of dendritic branches in vivo at the time when synapse formation takes place. These data reveal a novel function for the CD95 system and add to the picture of guidance molecules in the developing brain.
Published online: 08.7.05
Gesehen am 03.03.2021